Synthesis and Controlled Release Characterization of Zinc-Aluminium-Layered Double Hydroxide-Chlorophenoxyacetates Nanohybrids - Sarijo, Siti Halimah (2008)
The massive use of agrochemicals, such as herbicides has led to the contamination of these chemicals in the environment especially surface and ground-water reservoir. One approach to solve this problem is to develop controlled release agrochemical, in which the chemical is embedded into a matrix/support system, and can be released in a controlled manner. This study aimed at the synthesis of new controlled release of herbicides, namely 2-chlorophenoxyacetate, 4-chlorophenoxy-acetate and 2,4,5-trichlorophenoxyacetate via intercalation of the chlorophenoxyherbicides into zinc-aluminium-layered double hydroxide by self-assembly and anion-exchange methods. Upon the successful intercalation of the herbicides, release profiles and the factors govern its release from their matrices into various aqueous media were determined. In this study, relatively phase-pure with well ordered layered nanohybrid materials were successfully synthesized by both methods at optimum condition. Expansion of basal spacing was observed from 8.9 Å in the zinc-aluminium-layered double hydroxide to 18.5, 20.1 and 26.2 Å, in zinc-aluminium-2-chlorophenoxyacetate, zinc-aluminium-4-chlorophe- noxyacetate and zinc-aluminium-2,4,5-trichlorophenoxyacetate nano- hybrids respectively, obtained from self-assembly method, compared to 19.6, 19.5 and 25.8 Å, respectively, in the nanohybrids synthesized by anion-exchange method. Controlled release study of the herbicides into the aqueous solutions of sodium carbonate, sodium sulfate and sodium chloride as well as in distilled water at pH = 3, 6.25 and 12 is in the order of: 2-chlorophenoxyacetate > 4-chlorophenoxyacetate > 2,4,5-trichloro-phenoxy acetate. Release of herbicides into the aqueous media is in the order of: sodium carbonate > sodium sulfate > sodium chloride and pH 12 > pH 3 > pH 6.25. The release profiles are best described by pseudo-second order kinetic model as shown by the regression values of about 1.0. The 4-chlorophenoxyacetates anion was selectively intercalated into zinc-aluminium-layered double hydroxide than 2,4,5-trichlorophenoxyacetate, with percentage anion of 35.5 and 21.0 %, for 4-chlorophenoxyacetates and 2,4,5-trichlorophenoxyacetate, respectively while 2,4,5-tri-chloro-phenoxyacetate was preferably intercalated compared to 2-chlorop-henoxyacetates with the percentage loading of 57.8 and 31.4 %, respectively, for the latter and the former. This study shows that the zinc-aluminium-layered double hydroxide can be used as a matrix for controlled release formulation of chlorophenoxyacetic acid herbicides. The release of chlorophenoxyherbicides from the matrix was found to be controlled by the concentration and the anion in the release aqueous solution as well as the pH of the release media.